Magnetohydrodynyamic Flow for a Viscoclastic Fluid with the Generalized Oldroyd-B Model with Fractional Derivative - Rasan, Dhefaf (Iraqi Journal of Science, 2023)
This paper deals with the Magnetohydrodynyamic (Mill)) flow for a viscoclastic fluid of the generalized Oldroyd-B model. The fractional calculus approach is used to establish the constitutive relationship of the non-Newtonian fluid model. Exact analytic solutions for the velocity and shear stress fields in terms of the Fox H-function are obtained by using discrete Laplace transform. The effect of different parameter that controlled the motion and shear stress equations are studied through plotting using the MATHEMATICA-8 software.